Living matter—nexus of physics and biology in the 21st century - Gardel, Margaret L. (The American Society for Cell Biology, 2012)
Cells are made up of complex assemblies of cytoskeletal proteins that facilitate force transmission from the molecular to cellular scale to regulate cell shape and force generation. The “living matter” formed by the cytoskeleton facilitates versatile and robust behaviors of cells, including their migration, adhesion, division, and morphology, that ultimately determine tissue architecture and mechanics. Elucidating the underlying physical principles of such living matter provides great opportunities in both biology and physics. For physicists, the cytoskeleton provides an exceptional toolbox to study materials far from equilibrium. For biologists, these studies will provide new understanding of how molecular-scale processes determine cell morphological changes.